1999
DOI: 10.1067/msy.2099.100720
|View full text |Cite
|
Sign up to set email alerts
|

Initial experience with laparoscopic live donor nephrectomy

Abstract: LDN is technically feasible and safe, and recipient graft outcomes are equivalent. Convalescence is shortened, and there is less personal financial loss. LDN offers significant benefit to the donor and may result in increased organ donation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
42
0
4

Year Published

2001
2001
2006
2006

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(46 citation statements)
references
References 0 publications
0
42
0
4
Order By: Relevance
“…dian acceptable values for length of scar and length of stay were lower than average values reported for open nephrectomy in the literature. To date, promising data suggest that the laparoscopic procedure may address these concerns (17,(27)(28)(29).…”
Section: Discussionmentioning
confidence: 99%
“…dian acceptable values for length of scar and length of stay were lower than average values reported for open nephrectomy in the literature. To date, promising data suggest that the laparoscopic procedure may address these concerns (17,(27)(28)(29).…”
Section: Discussionmentioning
confidence: 99%
“…A review of previously published series (8)(9)(10)(16)(17)(18) showed that operative times ranged from 183 to 230 min for laparoscopic donor nephrectomies, and from 183 to 213 for open donor nephrectomies. Estimated blood loss ranged from 122 to 266 mL for laparoscopic procurements, and from 192 to 408 mL for open approaches.…”
Section: Patient #5mentioning
confidence: 99%
“…Laparoscopic live donor nephrectomy has been demonstrated to have several advantages when compared with open donor nephrectomy. They include but are not limited to shorter hospitalization, decreased pain measured by reduced analgesic requirements, an increased willingness of potential donors to undergo the procedure, and an earlier return to employment and full activities (5)(6)(7)(8)(9)(10)(11).…”
Section: Introductionmentioning
confidence: 99%
“…But subsequent studies have demonstrated that with increasing surgical experience, low technical complication rates can also be achieved with laparoscopic kidneys, regardless whether left or right kidneys (8), or kidneys with anatomical variations, such as multiple renal arteries, are used (9). Second, several investigators have shown slower early post-transplant function for laparoscopic (vs. open) grafts, as measured by delayed function rates (10)(11)(12) and by the recipients' early post-transplant serum creatinine levels (10,13,14). These findings are a priori not surprising, because warm ischemia times in laparoscopic donors are longer (11), and the pneumoperitoneum created during the laparoscopic operation negatively affects renal hemodynamics (15)(16)(17)(18).…”
Section: Introductionmentioning
confidence: 99%
“…Second, several investigators have shown slower early post-transplant function for laparoscopic (vs. open) grafts, as measured by delayed function rates (10)(11)(12) and by the recipients' early post-transplant serum creatinine levels (10,13,14). These findings are a priori not surprising, because warm ischemia times in laparoscopic donors are longer (11), and the pneumoperitoneum created during the laparoscopic operation negatively affects renal hemodynamics (15)(16)(17)(18). Slower early function in laparoscopic grafts, however, was not observed on all post-transplant days, did not persist beyond the first month, and did not achieve statistical significance at all time points in all studies (10,11,13,14,19,20).…”
Section: Introductionmentioning
confidence: 99%